Liver resection as part of cytoreductive surgery for ovarian cancer. - Luna-Abanto, J. (2020)
Objective: The aim of this study was to describe and evaluate the safety of hepatic resections for ovarian cancer liver metastases and the benefit in terms of survival as part of cytoreductive surgery among peritoneal seeding and parenchymal metastases. Materials and Methods: Data were reviewed retrospectively from patients who underwent liver resection as part of cytoreductive surgery for ovarian cancer at the Instituto Nacional de Enfermedades Neoplásicas, in Lima, Perú, from January 2009 to December 2017. Results: From January 2009 to December 2017, 1211 patients underwent surgical cytoreduction for ovarian cancer; 39 of these patients had liver resection as part of their surgical treatment, with 9, 17, and 13 patients receiving primary, secondary, and tertiary, resections, respectively. The mean age of the patients was 46, the majority (87%) had stage III/IV ovarian cancer. In addition, 21 patients had parenchymal metastasis resections, and 95% of the patients had Dindo-Clavien I and II grade complications. The 30-day mortality rate was 0. Conclusions: Liver resection for advanced ovarian cancer is a safe procedure for primary up to quaternary cytoreduction and may confer survival benefits to patients.